The impact of selected hog carcass traits on prices received - Mintert, J.; Dritz, Steven S.; Schroeder, Ted C.; Hedges, S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Hog producers can control the quality of the hogs they market. Through genetic selection and management, producers can have a large impact on hog carcass characteristics such as weight, backfat depth, and loin depth. Determining how much emphasis to place on changing or managing various carcass traits requires knowledge of the trait's value to the individual producer. Results from this study provide information on expected changes in price at one major midwestern packer associated with changes in carcass weight, backfat depth, and loin depth. Number of hogs marketed in each group did not affect net carcass value. However, these results might not apply to other packing companies that employ different pricing matrices.
Keywords: Swine; Carcass traits; Pricing